Mir Ahmed Khan 1st (1666-1695) the founder of Ahmedzai Dynasty and Royal Family his Role, Achievements and Contribution for the establishment of Kalat State (Balochistan) - Baloch, Farooq (Al-Burz, 2010)
The Baloch government formed in Soorab under the Mirwani’s a sub-tribe of Kambrani Tribe. The Baloch tribes are living in a huge are, but during the 14th and 15th centuries they were mostly dispersed and non-unified. The big powers of the surrounding areas of Balochistan like Iran, Central Asia, Sindh and India were more established and had formed government. Balochistan and its habitants were divided among these powers, and this situation was continued from the centuries, and the Baloch tribes were perfect strangers on their own homeland, Mirwani started their rule from the city of Soorab in the beginning of 15th century, after sometimes they defeated the Mongol governor and captured the area and city of Kalat, then they sifted their capital from Soorab to Kalat. Mirwani faced many difficulties for the establishment of their government in the area. They faced Jatts (Jattgal) and fought with them many times and escaped them from the area of Jhalawan, they also defeated Rind Lashar Baloch invaders. They defeated Mangols. Jatts and Rind and Lashars and secured their Dynasty, in the year of 1666 A.D after the death of Mir Hasan Mirwani, the Chiefs of Kambrani tribe3s gave the Chair of Khanate to a very young and brave man, named was Mir Ahmed. The objectives behind this Study are to search the achievements and contributions of a great Baloch ruler (Khan) Mir Ahmed Khan, who ruled 29 years on Balochistan and done unforgettable achievements and services. This study is descriptive in nature and the secondary sources were consulted for the purpose.